Caracterização estrutural da sequência metassedimentar da mina Aurizona - (MA) - FERREIRA, Malu Millena Martins (2019)
The Aurizona Mine is located in northeastern Brazil, coastal northwestern portion of the state of Maranhão, in the Godofredo Viana town. The mine is part of the geological context of the São Luís Craton, specifically in Aurizona Group. The São Luís Craton is interpreted as a fragment of the southern portion of the West African Craton which remained in the South American Platform after the fragmentation of the supercontinent Gondwana. The rocks of the Aurizona Group comprise a metavulcanossedimentar sequence composed by tuffs, rhyolites, metamafic, schists and phyllites, intruded by Suite Tromaí’s plutonic rocks. The exposed rocks in the Aurizona Mine are part of a metavulcanosedimentary sequence composed by metarythmytes, metagraywackes, metacherts and metavolcanic rocks with felsic composition, cuted by dikes and veins of different stages of placement. The metasedimentary rocks have primary bedding (S0) well preserved, which has preferred direction NE-SW and subvertical dip angle ranging between 70 ° and 85 ° NW and remains constant in both sides of the hole. In the metasedimentary rocks was developed a secondary foliation, characterized by spaced cleavage (S1), which has preferred direction 130 ° Az in the sounthern side of the hole and 050 ° Az in the northern side. A third foliation (S2) developed due to the installation of shear bands, sub concordant to the primary bedding. Along these shear bands are formed intrafoliation drag folds with dextral rotation. These rocks also underwent brittle deformation, which generated normal, inverse and directional failures. Although the presence of cleavage can indicate folds, no clear evidence of folds was found. The rock association seen in the mine is similar to a proterozoic greenstone sequence and may indicate a possibly correlation with Birimian Supergroup’s rocks in West African Craton.